Model based ranking of the influence of geometry and materials on the dynamical behavior of the violin highlights predominance of geometrical choices - Romain Viala; Vincent Placet; Emmanuel Foltête; Scott Cogan (Scientific Reports)
Abstract When considering the vibroacoustical behavior of the family of violin instruments, especially related to their construction, numerous beliefs and theories coexist that are not necessarily compatibles between each other. More specifically, the resulting sound or dynamics of the instrument are associated to tonewood properties and geometry, but with ranking and weights that vary according to beliefs and testimony of makers. This study presents an approach to understanding the relative influence of both geometrical and material properties on the vibrational dynamics of the violin. By conducting a screening analysis, using finite element method based computations of a complete violin, we explore impact of maker’s choices during the construction process. The results highlight that the dynamical behavior of the violin is mainly depending on geometrical choices, such as thickness of back and top plate or f-holes shapes, rather than the complete variability of properties of tonewoods. Therefore, the wood selection appears to be a second order effect compared to other luthier’s choices, supporting a craftsmanship practice and can pave the way to the use of lower grade woods, which are more in adequacy with what the resource can offer. This work offers new insights that can assist violin makers in optimizing their design choices and adapting to sustainable material use without compromising subsequent behavior.